2014
DOI: 10.1007/s11033-014-3721-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Platycodon grandiflorum germplasm resources from northern Anhui province based on ISSR analysis

Abstract: Based on genetic diversity analysis with ISSR-PCR, this study was to access the germplasm resources of Platycodon grandiflorum in northern Anhui province. Ten primers that could produce more distinct and repeatable bands were used for ISSR-PCR. Statistic analysis was conducted by POPGENE v. 1.32, Arlequin3.l, NTSYS-pc version 2.1. (1) Seventy-four polymorphic bands (76.29 %) out of a total of 97 were generated from 105 individuals in five populations. (2) Shannon index of diversity ranged from 0.307 to 0.260, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…High value have been reported in Portulaca oleracea (Ip = 0.515) (Alam et al, 2015). Further, the average value for PPBs was found to be 31.98% that was lower than that of Platycodon longiflorum (PPBs = 55.67%) (Nie et al, 2014). Low genetic diversity within populations has been reported in other plant species, such as Taxus fuana (Shah et al, 2008) and Monimopetalum chinense (Xie et al, 2005).…”
Section: Genetic Diversitymentioning
confidence: 84%
See 2 more Smart Citations
“…High value have been reported in Portulaca oleracea (Ip = 0.515) (Alam et al, 2015). Further, the average value for PPBs was found to be 31.98% that was lower than that of Platycodon longiflorum (PPBs = 55.67%) (Nie et al, 2014). Low genetic diversity within populations has been reported in other plant species, such as Taxus fuana (Shah et al, 2008) and Monimopetalum chinense (Xie et al, 2005).…”
Section: Genetic Diversitymentioning
confidence: 84%
“…It was observed that the genetic diversity of D. beecheyana var. pubescens (PPBs = 90.27%, Hes = 0.2497) at the species level was higher than that of the shortlived perennial species Blysmus sinocompressus (PPBs = 74.76%, Hes = 0.1668) (Hu et al, 2016) and mating breeding system species Platycodon grandiflorum (PPBs = 76.29%, Hes = 0.2326) (Nie et al, 2014). At the population level, the average Hep in D. beecheyana var.…”
Section: Genetic Diversitymentioning
confidence: 92%
See 1 more Smart Citation
“…From each cultivated plant population, a number of leaves were selected to accept the natural solar radiation. The gas exchange measurement (Nie et al, 2014) was carried out by a portable optical gas analysis system (LI-6400, Li-CorInc, Lincoln NE, USA). The control of the environmental factors in the leaf chamber was 20 °C, the concentration of the gas source…”
Section: Determination Of Photosynthetic Rate Of Leavesmentioning
confidence: 99%